Modeling In-Se amorphous alloys - Kohary, K; Burlakov, V; Pettifor, D; Nguyen-Manh, D (American Physical Society, 2005)
The structure of amorphous InxSey (a-InxSey) alloys has been studied by a first principles tight-binding molecular dynamics technique. The three dimensional amorphous structures with different densities at different compositions were prepared by quick quenching from the liquid phase. The characteristics of short-range order, namely radial distribution functions, coordination numbers, bond angle distribution functions, and the electronic structure have been analyzed. The local bonding environments of different InxSey crystals (in particular, In2Se3, InSe, and In4Se3) were found to be present in the amorphous phase. The average coordination number of indium is mainly four, whereas selenium is mostly two- or threefold coordinated. The majority of the bonds are heteropolar, but homopolar bonds are also present in a-InxSey so that they cannot be excluded from a realistic description of the amorphous structure. Larger content of indium in a-InxSey leads to an increased number of In-In bonds, as expected.